Methodological Proposal for the Assessment Potential of Pumped Hydropower Energy Storage: Case of Gran Canaria Island - Hilario J. Torres-Herrera; Alexis Lozano-Medina (Energies, 2021)
The pumped hydropower energy storage (PHES) assessments carried out so far have been focused on large water bodies obtained from global or restricted-use databases, or, on the other hand, on the application of methodologies to specific areas focusing on the detection of dams. In addition, many assessments do not include data optimization, or include it at the end of the process and are subject to the prior application of restrictions, often stipulated with subjective criteria. The aim of this article is to design a universal and easily applicable methodology for the assessment of viable PHES potential, which provides immediate and reliable results to assist in the energy planning of a given territory. It is classified in ravine basins, including an optimization before using the restrictions. The island of Gran Canaria is taken as the territory of application, whose density of dams is the highest in the world and whose share of hydroelectric energy is, at present, null; besides, no PHES studies have been carried out. The results show that the PHES potential in Gran Canaria is 5996 MWh after applying the optimization and all technical constraints. If all environmental constraints were rigorously applied, the island would have no possible pairing. The results demonstrate the importance of tailoring the restrictions to each particular territory.